THE EFFECT OF EXCHANGE RATES, JAKARTA SHARIA INDEX, GOLD PRICES, AND COMPOSITE STOCK PRICE INDEX ON THE NET ASSET VALUE OF SHARIA MUTUAL FUNDS IN INDONESIA WITH INFLATION AS A MODERATION VARIABLE IN THE 2021-2024 PERIOD - Purnomo, Andi; Bawono, Anton; Sholikhin, Muhammad (Faculty of Islamic Economic and Business (FEBI), Sayyid Ali Rahmatullah State Islamic University (UIN SATU) Tulungagung, 2025)
This research analyses the factors influencing the Net Asset Value (NAV) of Sharia mutual funds in Indonesia, with inflation serving as the moderating variable. The study utilizes secondary data from the Financial Services Authority (OJK), Bank Indonesia (BI), the Indonesia Stock Exchange (BEI), Statistics Indonesia (BPS), academic journals, and other sources for the period of 2021–2024. The data analysis employs Stationarity Tests, Moderated Regression Analysis (MRA), Classical Assumption Tests, and Statistical Tests. The results indicate that the exchange rate has a positive, but insignificant, effect on the NAV of Sharia mutual funds in Indonesia. At the same time, it also has a negative and significant effect on the NAV of Sharia mutual funds in Indonesia. The exchange rate, when moderated by inflation, has a negative and significant effect on the NAV of Sharia mutual funds. Furthermore, the Jakarta Islamic Index (JII), when moderated by inflation, has a positive and significant effect on the NAV of Sharia mutual funds. To obtain the best regression model, it is necessary to exclude a variable due to multicollinearity. These findings are expected to benefit investors and the government in selecting investment factors and formulating policies aligned with public welfare. Furthermore, this research is expected to enrich the literature in Islamic economics.